LIPID DISTRIBUTION IN THE MEAT OF JAU (Zungaro jahu) AND THE INFLUENCE OF STORAGE TEMPERATURE ON ITS FAT STABILITY - Coutinho, Nathalia; Mársico, Eliane Teixeira; Cinquini, Miguel; Silva, Flávio; Monteiro, Maria Lucia Guerra; Moraes, Ismar; Conte-Junior, Carlos (Archives of Veterinary Science, 2019)
The aim of this study was to determine the total lipid content in nine different body regions of jau catfish (Zungaro jahu), and evaluate the nutritional composition, energy value and lipid oxidation of jau meat during 15 days at 4°C, before (T1) and after freezing (T2) for 105 days at –20°C. The body regions were divided into anterior-dorsal (P1), anterior-medial (P2), anterior-ventral (P3), central-dorsal (P4), central-medial (P5), central-ventral (P6), posterior-dorsal (P7), posterior-medial (P8), and posterior-ventral (P9). Jau catfish contained high protein (20.17%), low lipid (0.60%) and low energy value (88.36 kcal 100g-1). The increase of malondialdehyde - MDA (0.2 to 2.5 mg MDA/kg) was more pronounced (P<0.05) after freezing period (T2). Among all body regions analyzed, ventral portions (P3, P6 and P9) presented highest total lipid content (P<0.05). Our study revealed that total lipid varies depending on body regions. Moreover, both refrigerated and frozen storage did not avoid MDA formation.